Perception of contractual risk allocation in the oil and gas contracts in Malaysia - Wan Zahari, Wan Mohd Zulhafiz (Inderscience Enterprises Ltd., 2018)
Oil and gas projects are risky undertakings, which may cause severe damages to property and the environment, not to mention, personal injury and death to personnel. Contractual provision such as an indemnity and mutual hold harmless clause is used as a tool in allocating the risks. However, as a consequence of the private and government litigation arising from the Macondo oil spill in the Gulf of Mexico in 2010, evidence suggests that operators generally are seeking to modify the established approach to liability allocation through individual contract negotiations with contractors. This scenario has significant and potentially adverse financial implications for the contractors and for the long-term sustainability of the industry. An empirical study was conducted to investigate the issues and problems with regard to contractual risk allocation in oilfield service contracts in Malaysia. The methodology employed in this paper will essentially be a combination of literature review and qualitative study.